The Problems of Indonesian Education Policy with the Change of Curriculum as an Effort to Improve the Ranking of Education Quality in the World - Bahri, Syaiful; Yanto, Murni; Baryanto; Asad, Muhammad Mujtaba (Journal of Pedagogy and Education Science, 2025)
The curriculum is a fundamental yet often overlooked aspect of education, serving as the core of the learning process. It must be evaluated innovatively and dynamically to align with technological advancements and evolving societal needs. As technology progresses, education must adapt to equip future generations with relevant skills for global competition. A flexible, student-centered curriculum is essential, tailored to learners’ needs, interests, and experiences. This study employs library research, analyzing books, journals, and articles to explore educational challenges in Indonesia, including curriculum issues, corruption in funding, limited teaching hours, and restrictive teacher autonomy in lesson design. Potential solutions are drawn from successful models in Finland, Germany, and Australia, whose adaptable and equitable education systems could offer valuable insights for Indonesia. By addressing these challenges through evidence-based reforms, Indonesia can enhance its educational framework, ensuring it meets contemporary demands while fostering student-centered learning.